Whole genome mRNA transcriptomics analysis reveals different modes of action of the diarrheic shellfish poisons okadaic acid and dinophysis toxin-1 versus azaspiracid-1 in Caco-2 cells. (February 2018) - Bodero, Marcia; Hoogenboom, Ron L.A.P.; Bovee, Toine F.H.; Portier, Liza; de Haan, Laura; Peijnenburg, Ad; Hendriksen, Peter J.M.
Abstract: A study with DNA microarrays was performed to investigate the effects of two diarrhetic and one azaspiracid shellfish poison, okadaic acid (OA), dinophysistoxin-1 (DTX-1) and azaspiracid-1 (AZA-1) respectively, on the whole-genome mRNA expression of undifferentiated intestinal Caco-2 cells. Previously, the most responding genes were used to develop a dedicated array tube test to screen shellfish samples on the presence of these toxins. In the present study the whole genome mRNA expression was analyzed in order to reveal modes of action and obtain hints on potential biomarkers suitable to be used in alternative bioassays. Effects on key genes in the most affected pathways and processes were confirmed by qPCR. OA and DTX-1 induced almost identical effects on mRNA expression, which strongly indicates that OA and DTX-1induce similar toxic effects. Biological interpretation of the microarray data indicates that both compounds induce hypoxia related pathways/processes, the unfolded protein response (UPR) and endoplasmic reticulum (ER) stress. The gene expression profile of AZA-1 is different and shows increased mRNA expression of genes involved in cholesterol synthesis and glycolysis, suggesting a different mode of action for this toxin. Future studies should reveal whether identified pathways provide suitable biomarkers for rapid detection of DSPs in shellfish. Highlights: OA and DTX-1 induced similar effects on mRNA expression in Caco-2 cells. OA/DTX-1 showed different gene expression than AZA-1. OA/DTX-1 induced hypoxia, unfolded protein response and ER stress. AZA-1 affected genes involved in cholesterol synthesis, metallothioneins and glycolysis.